Uma análise do ajuste da matriz energética brasileira às Conferências Mundiais de Meio Ambiente (1972-2002) - Rabbi, Douglas Silva (2011)
This study analyzes the adjustment of the Brazilian energy mix through public policies focusing on renewable energy sources, as a response to the three United Nations Conferences on the Environment held between 1972 and 2002. It shows the change of focus in the energy mix planning, which had been historically built by economic factors, due to pressure from organized national and international sectors. Therefore, we observed that the shift from valuing the economic dimension to valuing the environmental dimension during this historical study period is due to increasing impositions by sectors committed to sustainable development, in compliance with decisions made at those UN conferences. Thus, the strategy of “environmental alignment” of the Brazilian energy mix, which has been adopted by successive governments, contributed to consolidating Brazil"s position as a world leader in environmental sustainability. However, Brazil"s strategy is questioned because although its energy mix is environmentally adjusted, it still shows economic and social problems, especially concerning the universalization of access to energy until 2002.